The Combination of Salbutamol Nebulizer and Oral Procaterol to the Indonesian Children with Pneumonia: Role of Falcaria vulgaris on hippocampus - Darmawan, Endang; Kusumawati, Leny (Iranian Journal of Pharmaceutical Sciences, 2020)
This study aimed to examine the effectiveness of combining salbutamol nebulizer and oral procaterol compared to only oral procaterol on the respiratory rate, temperature (fever), spasm, cough frequency, thoracic retraction, and length of stay (LOS) among young children with pneumonia. This prospective cohort study included 48 consecutive sampling subjects with pneumonia in Indonesia. The subjects were classified based on the type of therapy they received: intervention group used the combination of salbutamol nebulizer and oral procaterol therapy (n=24 subjects) and the control group received oral procaterol only (n=24). The result showed that the combination therapy salbutamol nebulizer and oral procaterol was more effective than the administration of oral procaterol only with the rate of clinical change. Combination therapy nebulized salbutamol and oral procaterol significantly respiratory rate (p=0.006) and temperature (fever) (p=0.002) compared to the only oral procaterol. The combination had clinical change in reducing spasm, cough frequency, thoracic retraction, and length of stay (LOS) however there are was no significant effect of this combination in reducing spasm (p=0.348), cough frequency (p=0.964), thoracic retraction (p=0.666), and length of stay (LOS) (p=0.192) compared to the only oral procaterol among the Indonesian children with pneumonia.